Business Report: TIZ 6938 - Final Project and Internal Industrial Internship - Zamil Syah, Mustaffa (College of Arts and sciences, 2008)
This report is about Talian Tulen Sdn Bhd. It consist of company profile, business plan, sales achievement report, financial report and financial plan.